Epidemiology of invasive meningococcal disease in the Netherlands, 1960–2012: an analysis of national surveillance data - Bijlsma, Merijn W; Bekker, Vincent; Brouwer, Matthijs C; Spanjaard, Lodewijk; van de Beek, Diederik; van der Ende, Arie (The Lancet infectious diseases, 2014)
Epidemiological data for invasive meningococcal disease is essential for public health policy and vaccine development. We analysed national surveillance data from the Netherlands for PorA coverage of two PorA-based meningococcal serogroup B vaccines to describe the epidemiology of invasive meningococcal disease. We examined national surveillance data from the Netherlands Reference Laboratory of Bacterial Meningitis (NRLBM) for cases of culture-positive invasive meningococcal disease from Jan 1, 1960, to Jan 1, 2013. We included cases with a meningococcal isolate cultured from cerebrospinal fluid, blood, skin biopsy, or all, and cases with a positive cerebrospinal fluid latex agglutination test, counter current electrophoresis test, or positive cerebrospinal fluid PCR for Neisseria meningitidis. To test for completeness of case ascertainment, we compared data of the NRLBM with those of the Dutch National institute for public health and the environment (RIVM) to which notification was compulsory. We did serogrouping by ouchterlony gel diffusion. We tested susceptibility of meningococcal strains by agar dilution and E test. We tested differences between proportions with the Pearson χ2 test or Fisher's exact test, and differences in frequencies between time periods with the Mann-Whitney U test. We defined penicillin resistance as MIC of 1·0 μg/mL or higher. Annual incidence rates of invasive meningococcal disease per 100 000 population increased from 0·5 in 1960, to 4·5 in 2001, and subsequently decreased to 0·6 in 2012. Median age increased from 1·8 years in 1960, to 6·1 years in 2012 for all serogroups. The proportion of blood culture positive cases increased from 4% in 1960, to 60% in 2012 (p<0·0001). Serogroup B was the most common serogroup over time, 64% of isolates were from ST-41/44 complex. We established PorA finetype of 4133 isolates, 19 of 252 variable regions covered 99% of sequenced serogroup B cases. Coverage of the 4CMenB PorA component was 4% in 1960–65, and 36% in 2006–12. In response to a serogroup C epidemic (1999–2001), serogroup C conjugate vaccine was introduced, which reduced serogroup C disease by 95%. Since 2003, serogroup Y disease emerged and serogroup A disease disappeared. We identified evidence of capsular switching, but not of serogroup replacement. The rate of reduced penicillin susceptibility increased to 37% from 1993 to 2012, but penicillin resistance was not recorded. Incidence of invasive meningococcal disease has decreased, but decreasing rates of penicillin susceptibility and the possible resurgence of this devastating disease remain a threat to public health. Our long-term serosubtyping and porA sequencing data is valuable for the assessment of vaccine coverage and future serogroup B vaccine development. National Institute of Public Health and the Environment, the European Union's seventh Framework programme, Netherlands Organization for Health Research and Development, Academic Medical Center, and the European Research Council.